STRESS OXYDANT : INFLUENCE D’UNE COMPLEMENTATION NUTRITIONNELLE EN ANTIOXYDANTSET ADAPTATION A L’EXERCICE PHYSIQUE - F Chiha; Y Benkara; A Sellami; S Karouche (Revue des Sciences Humaines, 2016)
This study aims to highlight the knowledge of the state of oxidative stress, adaptation of athletes to oxidative stress and show the importance of supplementation with antioxidants for better support the health of athletes.